Integrated Analysis Reveals the Gut Microbial Metabolite TMAO Promotes Inflammatory Hepatocellular Carcinoma by Upregulating POSTN - Wu, Yonglin; Rong, Xingyu; Pan, Miaomiao; Wang, Tongyao; Yang, Hao; Chen, Xiejiu; Xiao, Zhenming; Zhao, Chao (Frontiers in Cell and Developmental Biology, 2022)
Liver cancer has a high mortality rate. Chronic inflammation is one of the leading causes of hepatocellular carcinoma. Recent studies suggested high levels of trimethylamine N-oxide (TMAO) may correlate with increased risk of inflammatory-induced liver cancer. However, the mechanisms by which TMAO promotes liver cancer remain elusive. Here, we established a model of inflammatory-induced liver cancer by treating Hepa1-6 cells and Huh7 cells with TNF-α. TMAO synergistically increased the proliferation, migration and invasion of Hepa1-6 cells and Huh7 cells in the presence of TNF-α. We conducted bulk RNA-Seq of the TMAO-treated cell model of inflammatory Hepatocellular carcinoma (HCC) and evaluated the influence of the differentially expressed genes (DEGs) on clinical prognosis using Kaplan-Meier Plotter Database and Gene Expression Profiling Interactive Analysis (GEPIA) database. Univariate and multivariate Cox regression analyses of tumor microenvironment and DEGs were performed using Timer2.0. Upregulation of POSTN, LAYN and HTRA3 and downregulation of AANAT and AFM were positively related to poorer overall survival in human liver cancer. Moreover, higher expression of POSTN and HTRA3 positively correlated with infiltration of neutrophils, which can promote tumor progression. In vitro experiments showed TMAO activates ILK/AKT/mTOR signaling via POSTN, and knocking down POSTN significantly reduced ILK/AKT/mTOR signaling and the tumorigenicity of Hepa1-6 cells and Huh7 cells. Collectively, our results suggest the gut microbial metabolite TMAO and POSTN may represent potential therapeutic targets for liver cancer.